Carbon nanotubes and related structures : - Harris, Peter J. F. (Cambridge University Press, 2003)
Carbon nanotubes are molecular-scale carbon fibers with structures related to those of the fullerenes. Since their discovery in 1991, they have captured the imagination of physicists, chemists and materials scientists alike. This book covers all the most important areas of nanotube research, as well as discussing related structures such as carbon nanoparticles and "inorganic fullerenes." It is the first single-author book on the subject and will be of interest to chemists, physicists, materials scientists, and engineers working on carbon materials and fullerenes in both academia and industry